För ung för string? - Viveka Bergren Torell (Kulturella Perspektiv, 2005)
Girls' clothes — especially string briefs — seen by adults as sexualizing fashion are debated among both adults and children. In this article letters to the editors of a daily paper, written by adults, are seen as connected to a large discussion about the threats against childhood. For many adults what they see as sexy garments for girls become examples of how sexual expressions from the adult world takes innocence out of childhood. Maybe adults would be less afraid if they knew how children themselves interpret girls' fashion? That question came up inspired by the so called new childhood research — where children are seen as active in creating their own meanings on different phenomena. The second half of the article is about string briefs as debated in the Swedish children's magazine "Kamratposten". The analysis here draws on the sociologist Fred Davis' theories that people through their use of clothes do not express their feelings of an inner personal identity, but first and foremost express and work on different ambivalences regarding social identity. Girls seem to debate and use string briefs to work on ambivalences about age and maturity, being a "groupmember" or not, the esthetisation fo the body and about how to express femininity. Partly the farment is used within age specific material practices, but the debate also reflects different adult feminist standpoints on fashion.